Analisis Butir Soal pada Instrumen Asesmen Kompetensi Minimum Literasi Membaca di SMP IT Insan Utama Pekanbaru - Della Putri Andini; Muhammad Mukhlis (Universitas Mulawarman, 2023)
Minimum Competency Assessment (AKM) assesses fundamental skills required for all students to help them improve their skills and participate actively in society. The AKM aims to identify assessment data or reports on students' understanding of the material. The AKM is very important for teachers because it provides an objective measure of learning performance, and for students, the results of this assessment indicate their level of learning achievement. This study aims to describe the results of the analysis of the AKM reading literacy items at SMP IT Insan Utama Pekanbaru. The research method used is a descriptive qualitative method with content analysis. Based on the study's results, the percentage results of the difficulty level analysis of the guiding items were that 70% of the questions were categorized as difficult, 25% were moderate, and 5% were easy. It means that too many questions are difficult. The results of the calculation of differentiating power show that 40% of the questions are very good, 20% are good, 10% are sufficient, and 30% are bad. The analysis of the effectiveness of the checkers shows that 5% of the questions are very good, 15% good, 10% not good enough, 20% bad, 15% very bad.